2019
DOI: 10.1007/s42452-019-1844-y
|View full text |Cite
|
Sign up to set email alerts
|

Establishing relationship between fusion zone hardness and grain size of gas tungsten constricted arc welded thin sheets of titanium alloy

Abstract: Ti-6Al-4V alloys are perfectly suited for fan compressor blade material in advanced aero engine components due to outstanding resistance to corrosion and specific strength was high in both room temperature and elevated temperature. For autogeneous welding of thin sheets of Ti-6Al-4V alloy, the gas tungsten constricted arc welding (GTCAW) was established to be beneficial than the gas tungsten arc welding process. The performance of welded joints depends on the fusion zone grain size (FZG) and fusion zone hardne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Coarse grains are associated with lower hardness due to less grain boundaries within the fixed indentation area. A similar observation in gas tungsten constricted arc welding was also reported by Vaithiyanathan et al (2020) [26].…”
Section: Microhardness Of Weld Bead and Hazsupporting
confidence: 86%
“…Coarse grains are associated with lower hardness due to less grain boundaries within the fixed indentation area. A similar observation in gas tungsten constricted arc welding was also reported by Vaithiyanathan et al (2020) [26].…”
Section: Microhardness Of Weld Bead and Hazsupporting
confidence: 86%
“…Leary et al [14] practised GTCAW process for joining of Ti6Al4V alloy without the need of trailing gas shield and concluded that magnetic arc constriction technique extends better microstructural evolution of weld relative to normal GTAW as a result of lower heat input. Vaithiyanathan et al [15] stated that pulsing current at high frequency eliminated the evolution of widmanstatten structure in weld metal leading to superior strength in GTCA welded Ti6Al4V sheets relative to GTAW process. InterPulse current frequency extends significant influence on grain size and hardness of fusion zone in GTCA welded Ti6Al4V joints [16].…”
Section: Introductionmentioning
confidence: 99%
“…The published literature mainly pertains to gas tungsten arc welding (GTAW) [20][21][22], electron beam welding (EBW) [23][24][25] and laser beam welding (LBW) [26][27][28] of Inconel 718 alloy. The investigations on GTCA welding process are limited to titanium alloys [12][13][14][15] and steel [16,17]. In the previous investigation [18], GTCAW process was successfully used to join 2-mm-thick Inconel 718 alloy sheets.…”
Section: Introductionmentioning
confidence: 99%